Management of localized gingival recession by two-stage surgical procedure - Double pedicle flap with CTG and coronally advanced flap: A novel technique - Prasanth T (Journal of Indian Society of Periodontology, 2009)
Cosmetic treatments have become an integral part of periodontal treatment. One of the commonly used esthetic periodontal procedures is coverage of denuded root surface. While considering the elimination of these defects two criteria should be considered, the esthetic aspects and the functional aspects. This case report has describes a two stage surgical technique using double pedicle flap with connective tissue graft followed by coronally advanced flap for the treatment of a severe localized gingival recession measuring 15 mm. The recession measurement at the end of 12 months was 1 mm. It showed a predictable result at the end of one year. The advantages of this technique are excellent colour matching, dual blood supply to graft and very predictable results. The promising result suggest that this technique can be used in severe gingival recession cases with minimum amount of keratinized tissue.